Lack of Serotype Antigen in A. actinomycetemcomitans - DOĞAN, BAŞAK (SAGE PUBLICATIONS INC, 2010)
Aggregatibacter actinomycetemcomitans is divided into 6 serotypes. Occurrence of non-serotypeable strains is known, but background reasons are unclear. We hypothesized that non-serotypeable strains represent new serotypes or have altered expression of serotype-specific polysaccharide antigen (S-PA). We first characterized 311 strains from 189 individuals using both immunoassay-and PCR-based serotyping. Next, using natural human infection and rabbit immunization approaches, we clarified whether the phenotypically non-serotypeable strains expressed S-PA. Immunoassay identified serotypes a-f among 216 strains from 159 individuals. The remaining 95 strains from 30 individuals were phenotypically non-serotypeable. Yet, all these strains were identified by PCR-typing as serotype a-, b-, c-, or f. Non-serotypeability was confirmed by Western immunoblot with respective rabbit antisera. Patient sera remained non-reactive with autologous non-serotypeable strains at the serotype-specific region. Rabbit immunization with a phenotypically non-serotypeable strain induced no antibody production against S-PA. Thus, phenotypically non-serotypeable strains did not include novel serotypes, but lacked S-PA expression.
Keywords: A. actinomycetemcomitans; serotype antigen; non-serotypeability; periodontitis; gene expression; HUMAN PERIODONTAL-DISEASE; ACTINOBACILLUS-ACTINOMYCETEMCOMITANS; AGGREGATIBACTER-ACTINOMYCETEMCOMITANS; PORPHYROMONAS-GINGIVALIS; JUVENILE PERIODONTITIS; O-POLYSACCHARIDE; LIPOPOLYSACCHARIDE; STRAINS; COAGGREGATION; POPULATION